Preparation of pH and redox dual-sensitive core crosslinked micelles for overcoming drug resistance of DOX. Issue 9 (1st February 2016) - Yi, Xiao-Qing; Zhang, Quan; Zhao, Dan; Xu, Jia-Qi; Zhong, Zhen-Lin; Zhuo, Ren-Xi; Li, Feng
Abstract : When incubating the pH and redox dual-sensitive CCL/SS micelles with MCF-7/ADR cells, they could sufficiently overcome drug resistance to deliver DOX into MCF-7/ADR cells, leading to the apoptosis of tumor cells. Abstract : In this paper, we first synthesized an amphiphilic block copolymer poly(ethylene glycol)-poly(2, 4, 6-trimethoxybenzylidene-pentaerythritol carbonate- co -5-methyl-5-propargyl-1, 3-dioxan-2-one), i.e., PEG-P(TMBPEC- co -MPMC), with pendant reactive alkynyl groups as well as pH-sensitive acetal groups. Next, core crosslinked (CCL) micelles were prepared by the introduction of 1, 6-diazidohexane and bis(azidoethyl)disulfide into micelles via azide–alkyne click chemistry, which were denoted as CCL/CC and CCL/SS, respectively. The CCL micelles had superior stability and drug loading efficiency to the uncrosslinked (UCL) micelles. In comparison with free DOX, drug-loaded CCL micelles exhibited lower cell viability in MCF-7/ADR cells due to their "stealth" endocytosis effect that might be beneficial for overcoming delivery barriers of drug resistance. More interestingly, as compared with CCL/CC micelles, CCL/SS micelles were found to further enhance cytotoxicity in MCF-7/ADR cells because of their better on-demand drug release capability of pH and redox dual-sensitive CCL/SS micelles. These results suggest that the self-assembled pH and redox dual-sensitive CCL/SS micelles have promising applications to overcome multi-drug resistance in tumor treatments.